Hepatic Artery Microvascular Anastomosis in Liver Transplantation: A Systematic Review of the Literature. Issue 1 (January 2021) - Kantar, Rami S.; Berman, Zoe P.; Diep, Gustave K.; Ramly, Elie P.; Alfonso, Allyson R.; Sosin, Michael; Lee, Z-Hye; Rifkin, William J.; Kaoutzanis, Christodoulos; Yu, Jason W.; Ceradini, Daniel J.; Dagher, Nabil N.; et al.
Abstract : Background: The operating microscope is used in many centers for microvascular hepatic arterial reconstruction in living as well as deceased donor liver transplantation in adult and pediatric recipients. To date, a systematic review of the literature examining this topic is lacking. Methods: This systematic review of the literature was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Three different electronic databases (PubMed, Embase OVID, and Cochrane CENTRAL) were queried. Results: A total of 34 studies were included. The rate of hepatic artery thrombosis (HAT) in noncomparative studies (28) ranged from 0% to 10%, with 8 studies reporting patient deaths resulting from HAT. Within comparative studies, the rate of HAT in patients who underwent arterial reconstruction using the operating microscope ranged from 0% to 5.3%, whereas the rate of HAT in patients who underwent arterial reconstruction using loupe magnification ranged from 0% up to 28.6%, and 2 studies reported patient deaths resulting from HAT. Two comparative studies did not find statistically significant differences between the 2 groups. Conclusions: Our comprehensive systematic review of the literature seems to suggest that overall, rates of HAT may be lower when the operating microscope is used for hepatic arterial reconstruction in liver transplantation. However, matched comparisons are lacking and surgical teams need to be mindful of the learning curve associated with the use of the operating microscope as compared with loupe magnification, as well as the logistical and time constraints associated with setup of the operating microscope.